The social construction of human kinds - Almeida, Guilherme de Cesáris (Sapere Aude, 2015)
Resenha do artigo SVEINSDÓTTIR, ÁSTA KRISTJANA. THE SOCIAL CONSTRUCTION OF HUMAN KINDS. HYPATIA, V. 28, N. 4, p. 716-732, 2013.